CHARLES DICKENS AS A SOCIAL NOVELIST: LIFE EXPERIENCE AND LITERARY DEVELOPMENT - Izzatilloyeva Mohichehra Baxtiyorovna, (TADQIQOTLAR, 2026)
Abstract. Charles Dickens occupies a central place in Victorian literature as a novelist who transformed personal hardship into powerful social commentary. This article examines Dickens's development as a social novelist through the interaction of his  life  experience  and  literary  evolution.  Drawing  on  his  early  encounters  with poverty, child labor, and institutional injustice, Dickens created a body of fiction that exposes  social  inequalities  while  appealing  to  moral  responsibility  and  human compassion.  The  study  analyzes  how  Dickens's  biography  influenced  his  thematic concerns, narrative techniques, and reformist vision, highlighting his role in shaping the social conscience of nineteenth-century England.